DUKUNGAN REVOLUSI MENTAL DALAM UPAYA MEMBENTUK ANAK HEBAT DAN TANGGAP - Nur Imamah, Ida; Wijaya Gati, Norman (P3M STIKES Aisyiyah Surakarta, 2017)
School age children is where townhouse needed a good accompaniment in children. Mentoring is necessary to ensure the child is able to perform is development. The implementation of activities that teachers have a target servicecadres and elderly. The activities undertaken with the approach of the model of stress adaptation in Stuart. This approach models with adaptative and maladaptive response look. Outreach activities carried out on Thursday, August 3, 2017 started at 9 a.m. activities are implemented in the class room SDN Gonilan 02 Kartasuro Sukoharjo, followed by 7 teachers and 72 students composed of 3,4 and 5 classes with matter ?How to be a Child?. Closed activities by providing reserved post test result and 83,3 % of the students answered correctly the question asked. Based on result of the post can be said knowledge test children increased 25 % compared to the result of a test that showed pre 58,3%.